An Intranasal Vaccination with a Recombinant Outer Membrane Protein H against Haemorrhagic Septicemia in Swamp Buffaloes - Anucha Muenthaisong; Boondarika Nambooppha; Amarin Rittipornlertrak; Pallop Tankaew; Thanya Varinrak; Korkiat Muangthai; Kheemchompu Atthikanyaphak; Takuo Sawada; Nattawooti Sthitmatee (Veterinary Medicine International)
Hemorrhagic septicemia (HS) is an important infectious disease in cattle and buffaloes, caused by Pasteurella multocida B:2 and E:2. The intranasal recombinant OmpH-based vaccine was successfully used to protect dairy cattle from HS in a previous study. Thus, this study aimed to examine the protective ability of that vaccine among buffaloes. Four groups of Thai swamp buffaloes received different vaccines and were labeled as 100 or 200 μg of the rOmpH with CpG-ODN2007, commercial HS bacterin vaccine, and nonvaccinated control groups. Sera and whole blood were collected to examine the antibody levels and cellular immune response using indirect ELISA and MTT assay, respectively. Challenge exposure was performed with virulent P. multocida strain M-1404 serotype B:2 on day 72 of the experiment. The antibody titers to P. multocida among immunized buffaloes were significantly higher than in the control group (p<0.01), especially the 200 μg of the rOmpH group. The stimulation index (SI) of the intranasally vaccinated groups revealed significantly higher levels than the nonvaccinated group (p<0.01), but not different from the intramuscularly commercial HS vaccine. The clinical signs and high fever were observed after challenge exposure in the nonvaccinated group, while it was not observed among the 200 μg of rOmpH immunized buffaloes. The other immunized groups showed partial protection with transient fever. In conclusion, the rOmpH-based intranasal vaccine could elicit protective ability and induce antibody- and cell-mediated immune response against virulent P. multocida strain among swamp buffaloes.